POLITICAL EMPOWERMENT OF WEST JAVA PDI-P WOMEN’S CADRES IN THE 2024 LEGISLATIVE ELECTION - Nurfebriansyah, Ahmad Rifki; Rahmatunnisa, Mudiyati; Solihah, Ratnia (Universitas Padjadjaran, 2025)
The involvement of women in political parties cannot be ignored. This is because gender equality allows democracy to function properly. PDI-P is the only party that has the highest level of women participation. West Java is one of the crucial provinces in both the 2024 General Election or Regional Election. This study aims to explore how women’s empowerment is carried out by PDI-P West Java in each stage of their politics and what the results are. Qualitative research is conducted by collecting primary and secondary data. Primary data is conducted by interviewing selected informants and secondary data trough related document. Data validation is conducted by triangulation sources to check the data obtained. The results of the study show that PDI-P West Java has carried out various methods of empowering women, such as setting party rules regarding women’s quotas in party membership, and candidates who advance in legislative elections, holding special activities for women, providing financial assistance and campaign training for women, and providing training for women cadres who sit in parliament. The results also show that women legislators from the PDI-P West Java faction are very active in speaking out in parliament.